Axial performance of grouted C-Shaped concrete block masonry columns jacketed by carbon and glass FRP. (15th September 2022) - Alotaibi, Khalid Saqer; Saiful Islam, A.B.M.; Galal, Khaled
Highlights: Scaled C-shaped concrete blocks masonry confined with CFRP and GFRP jackets tested under concentric compressive load. The results for different numbers of layers and FRP materials with three replicas for each combination. The predictions of Eight theoretical models were compared with experimental tests. Abstract: To overcome the relatively low ductility and capacity of masonry elements, the confinement technique may be an effective alternative for improving their performance, especially the columns. Fiber Reinforced Polymers (FRP) jacketing is a potential approach has benefits in terms of strength enhancement and gaining ductile behavior. Therefore, in this study, two types of FRP were used to improve column axial capacity and ductility: carbon and glass FRP. The effect of FRP wrapping on the compressive behavior of concrete masonry columns was investigated experimentally. Fully grouted scaled masonry columns constructed using C-shaped concrete blocks were wrapped with FRP jackets and tested under concentric compressive load until failure. For this purpose, 18 half-scale masonry prisms under variations in FRP jacketing and FRP thickness were developed and tested in six sets. The effect of FRP confinement on the unconfined masonry columns was evaluated. The CFRP and GFRP jacketing increased the peak strength and ultimate axial strain. Confinement improves post-peak performance by softening the descending stress–strain relationships. Increasing FRP jacket thickness improved the axial strain, strength, and ductility of masonry columns. The CFRP wrap gives 10 ∼ 16% more strength than GFRP. Ultimate strain enhanced by 76 % and 57 % for CFRP and GFRP respectively.